Integrating Inquiry Across the Curriculum. - Audet, Richard H. (SAGE Publications, 2005)
Inquiry is the fundamental first step in the learning process, and oftentimes the least understood. This finely edited volume enables educators to visualize inquiry as the unifying knowledge base to guide students through all major subject areas. It's a must-have guide for exploring ways to integrate concepts across different content areas.